Wealth management and divorce: how stress adjustment affects the accumulation, management and distribution of wealth - Kothakota, Michael Gerard (Kansas State University, 2019)
The dearth of research on short and long-term effects of divorce on financial behaviors warrants further investigation. This study investigates the effects of divorce on precautionary and retirement savings, proportion of assets in risk investments, and bequest intentions. Using data from the Panel Study on Income Dynamics from the University of Michigan Center for Social Research, exponential fractional regression models (EFRM) were specified to examine changes in savings behaviors and risky asset share post divorce. Binary logistic regressions were specified on bequest intentions for leaving assets to children, religious organizations, and non-religious charities. For all subgroups, precautionary savings behaviors and retirement savings intially decreased post-divorce, then stabilized and increased in later years. Similarly, for all subgroups risky asset share decreased over time. Sub-analyses also indicate differences between divorced individuals for single income versus double income households, as well as differences between the sexes. Divorced individuals were more likely to hold bequest intentions for children and less likely to bequest to religious and non-religious organizations than married individuals. Practical implications are discussed and recommendations for future research are provided.
Keywords: Divorce; Wealth management; Savings; Risky asset share; Fractional response models